PERAN MASYARAKAT DALAM PENGELOLAAN DESA WISATA ENDE SEBAGAI PARIWISATA BUDAYA DI KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Aditya Miftachul Dwirama; Mahsun Mahsun; I Putu Gede (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
This study discusses “The Role Of The Community In The Management Of Ende Tourism Village As Cultural Tourism In Pujut District, Central Lombok Regency”. This research was conducted to answer the problems that became the focus of research, namely regarding the form of the community’s role and its managemet in managing the Ende tourism village. The data were collected by using observation, interviews and documentaion with a techniques qualitative descriptive approach. The results of this study indicate that the management model of the Ende tourist village is purely carried out by the local community and carries out direct tourism activities in the Ende tourist village and forms its role as an object as well as a subject, which means that in the implementation of tourism activities, the community becomes tourism actors and managers, as well as objects that can be enjoy by tourist through performing arts attractions.